Theravada Buddhism - Abhayawansa, Kapila (Poligrafi, 2022)
Sri Lanka is the only country that has seen Theravada Buddhism established, preserved, and continue to exist up to the present since the missions to other co-untries from its birth in India. It is a historical fact that after the Third Buddhist Council, missionaries were dispatched to nine countries for the propagation of Theravada Buddhism. There is no historical evidence to confirm that any of the nine countries except Sri Lanka was able to preserve Theravada Buddhism and keep it in its original form throughout the course of time. On the other hand, Sri Lanka secures the honour and credit to have been the centre of Theravada Budd-hism for a considerable time.The present paper deals with the way Sri Lanka contributed immensely to the establishment, protection, and flourishing of Theravada Buddhism as a unique tradition of Buddhist thought. In this respect, our attention is focused mainly on the exegetical literature of the Theravada tradition which will shed much li-ght on both the theoretical and practical aspects of the tradition. The Sri Lankan Mahavihara community of monks was responsible for providing a vast exegetical literature which consists of commentaries, sub-commentaries, sub-sub-commen-taries, and the compendiums based on the Theravada canon brought to Sri Lanka. The writing down of the Theravada Pa?i canon in Sri Lanka for the first time also marks a unique event in the history of Buddhism. The contribution made by Sri Lanka to preserve the Pa?i canon by this means was highly instrumental in preser-ving it in its original form. Further, Sri Lanka was a source of inspiration to other Theravada Buddhist countries to revitalize their Buddhism in accordance with the more orthodox form of Theravada.
Keywords: Buddhism; budizem; Chinese religion; kitajska religija; manuals; Pa?i Canon; palijski kanon; priročniki; teravadski budizem; Theravada Buddhism